Development and Validation of the Temperament and Affectivity Inventory (TAI). (October 2015) - Watson, David; Stasik, Sara M.; Chmielewski, Michael; Naragon-Gainey, Kristin
Trait affect scales have been a mainstay of the assessment literature for more than 50 years. These scales have demonstrated impressive construct validity, including substantial relations with personality, satisfaction, and psychopathology. However, the accumulating evidence has exposed several limitations, including (a) problems associated with retrospective biases, (b) lower temporal stability because of enhanced susceptibility to transient error, and (c) reduced self–other agreement. These limitations motivated the creation of the Temperament and Affectivity Inventory (TAI), which uses a traditional personality format (i.e., full sentences rather than single words or short phrases). The 12 TAI scales were created based on factor analyses in two samples and validated in four additional samples. The scales are internally consistent, highly stable over time, and show strong convergent, discriminant, and incremental validity in relation to self-report and interview-based measures of personality and psychopathology. Thus, the TAI provides a promising new approach to assessing trait affectivity.